La necesidad de garantizar por medio de la política salarial, el derecho a la vida digna de las personas que trabajan, y padecen de enfermedades catastróficas. - Trujillo Trujillo, Livia Judith (2015)
Among the problems of the social reality we find in our country the basic rights to human dignity and life of the workers, who in some cases suffering from catastrophic illnesses and are relegated or dismissed for such a condition is not guaranteed. For the effect on labor legislation, which between employers and workers, the legal benefits. This compulsory social insurance in case of accidents or occupational risks, but it is not considered aid or solidarity when the worker suffers catastrophic illness, so the basic principles of a decent life are violated. Therefore the Government through labor agencies and authorities should consider equity and inclusion through the wage policy to ensure this type of accuses fundamental rights of people with catastrophic illnesses. The fundamental rights of workers are based on principles and rights that are guaranteed in the Constitution and in international instruments to which our state is a part. It is important to ensure the development of social work law creating legal certainty in favor of the employee or worker suffering from catastrophic illnesses.